Apolipoprotein E-dependent cholesterol efflux from macrophages: kinetic study and divergent mechanisms for endogenous versus exogenous apolipoprotein E - Chen-Yi Lin; Hongwei Duan; Theodore Mazzone (Journal of Lipid Research, 1999)
In these studies, we have utilized a J774 macrophage model in order to compare phospholipid and cholesterol efflux kinetics in macrophage cells that do not express endogenous apoE to cells transfected to express physiologic levels of human apoE. This model was also used to compare the effect of exogenously added versus endogenously expressed apoE on cholesterol efflux kinetics from macrophages. ApoE expression increased free cholesterol and phospholipid efflux into the medium, but did not change the free cholesterol/phospholipid molar ratio of secreted lipids. Kinetic examination showed that free cholesterol and phospholipid appeared simultaneously in the medium, and that cholesterol loading widened the difference in the rate of cholesterol efflux between apoE-expressing and non-expressing macrophages. Addition of exogenous lipid-free apoE added to non-expressing cells, at a >2-fold higher medium concentration than that produced by endogenous expression, produced less cholesterol efflux than that observed from apoE-expressing cells. The addition of phosphatidylcholine liposomes substantially increased cholesterol efflux from apoE-expressing and non-expressing J774 cells. Addition of these liposomes eliminated the enhanced cholesterol efflux produced by addition of exogenous apoE. On the other hand, even in the presence of phosphatidylcholine liposomes, cholesterol efflux rates remained significantly higher from apoE-expressing macrophages than non-expressing cells. Similar results were obtained when efflux was studied in the presence of cyclodextrin. These results suggest that endogenous expression of apoE by macrophages alters cell cholesterol balance via mechanisms distinct from those utilized by the extracellular addition of apoE, and may involve intracellular or pericellular mechanisms.—Lin, C-Y., H. Duan, and T. Mazzone. Apolipoprotein E-dependent cholesterol efflux from macrophages: kinetic study and divergent mechanisms for endogenous versus exogenous apolipoprotein E. J. Lipid Res. 1999. 40: 1618–1626.